Analysis of the self-medication profile in COVID-19 pandemic in Brazil - Pitta, Marina Galdino da Rocha (2021)
This manuscript aims to analyze the brazilian profile of self-medication during the COVID-19 pandemic and to collect sociodemographic informations related to the self-medication. Therefore, it was necessary to investigate the concept of what participants understand about self-medication, in addition to examining what type of medication is used by those who self-medicated and it’s side effects. A research was carried out from August 3 to September 30, 2020. The samples were centered on who lived in Brazil. The interviewees should be at least 18 years old. The study included people from the general population. The data collection took place through an online questionnaire, because at that time the presential interviews should be avoided due to the continuous lockdown. To collect data from 1000 participants for this research. The drugs that prevailed belong into the class of vitamins and, secondly, Ivermectin. The indication of self-medication by family members was enhanced. The highest rates of reported side effects were intestinal colic and discomfort. The act of self-medication in Brazil was worrying in the pandemic period caused by COVID-19. Furthermore, it is important to emphasize that the population becomes aware and discerning about the sources of information that discuss the medications, thus avoiding hasty decisions that can be more harmful.